Wireless pressure sensor system for fish quality monitoring - B. Mu; M. A. Nikitina; X. Xiao (Теория и практика переработки мяса, 2022)
Food quality monitoring is increasingly important. This paper aims to propose the developed wireless pressure sensor system (WPSS) for fish quality monitoring. WPSS consists of a sensor acquisition module, power supply module, and Bluetooth module. The sensor acquisition module includes a temperature sensor, pressure sensor, and microcontroller unit (MCU). When Bluetooth receives the data collection command from the smartphone, the data of storage temperature and pressure in the food package can be collected by the sensor and transmitted wirelessly to the smartphone through Bluetooth. All data obtained by the system is monitored, stored, processed, and eventually displayed in a smartphone app in real-time to improve temperature, air pressure, and freshness transparency within the food package, ultimately ensuring food quality and safety. The proposed WPSS has potential application in many kinds of food monitoring. It can realize simple and intuitive food quality indications.